Food tissues as reward for birds - Roitman, Germán (2002)
Nectar is the reward regularly offered by flowers to their pollinating birds. Studies on pollinalion by birds have focused on nectar as a reward while alternative reward systems have been poorly studied. Previous reviews have shown the presence of food tissues that serve as nutritive rewards lo different classes of pollinators. However, in a recent revision of plant-bird interactions, the exist~ce of a solid reward for birds has been disregarded. In South America at least lhree cases of this very particular bird-flower interaction have been recently sludied. In this paper we describe lhe syndrome features (flower morphology, reward properties, position of the pollination unit, flower color display and common visitors), that deviate from the typical omithophilous syndrome, and its possible origin is discussed.